Contribution of epigenetic landscapes and transcription factors to X-chromosome reactivation in the inner cell mass - Maud Borensztein (Nature Portfolio, 2017)
X-chromosome inactivation is reversed in the mouse inner cell mass (ICM) through a mechanism that is not fully understood. Here, the authors investigate this process and characterize the contributions of the epigenetic landscape and transcription factors in X-linked gene reactivation dynamics.